Therapeutic Strategies in African Religions: Health, Herbal Medicines and Indigenous Christian Spirituality - Asamoah-Gyadu, J. Kwabena (Studies in World Christianity, 2014)
The use of herbs has been the main means of curing diseases in traditional Africa and this continued through the colonial period to present times. Widely held traditional views that interpreted certain diseases as caused by supernatural agents meant that, although some ailments could be naturally caused, in most cases, shrine priests and diviners were needed to dispense herbal preparations for clients. Christian missionaries mostly - though by no means all - denounced herbal medicines as evil, looking on them as pagan because of the close relationship between herbs and agents of local divinities. At the emergence of the African independent church movement at the beginning of the twentieth century, herbal medicines acquired a sacramental value, and today they are obtained from churches and local prophets as therapeutic substances infused with spiritual power for healing. The sacramental interpretation of herbs has been extended to those obtained from prayer places and grottoes under the supervision of historic mission denominations, a phenomenon that has virtually transformed the image of herbs and herbal medicines in African therapeutic systems.
paid
Keywords: AFRICA; ALTERNATIVE medicine; BABALAWOS; CHRISTIAN spirituality; Holy Spirit; INDEPENDENT churches; MEDICINE; MISSIONARIES; RELIGIOUS aspects; Spiritual churches; babalawo; diviners; grottoes; healing; herbal; medicines; prophet; shrines; therapeutic